Who Built Tel Rekhesh? - Hasegawa, Shūichi (The Biblical archaeology review, 2020)
After the Assyrian conquest of the northern Kingdom of Israel and deportation of its people in 722 B.C.E., who lived in the land? A large building complex at Tel Rekhesh hints that the new inhabitants came from Mesopotamia.